The Implementation of Mathlak in Determining the Beginning of the Lunar Month of the Majelis Pengkajian Tauhid Tasawuf Indonesia (MPTT-I) - Mustaqim, Riza Afrian; bin Adnan, Boihaqi; Khawatinnisa, Husnul; Hayana, Cut Diva; Sausan, Rahma Dhiyaa (University of Muhammadiyah Sumatera Utara, 2024)
Matlak in the determination of the beginning of the Kamariah month of the Majelis Pengkajian Tauhid Tasawuf Indonesia (MPTT-I) is often different from other methods. The conventional rukyat system and the limited scope of matlak are the causes of the dynamics, even in conditions of high hilal visibility differences still occur, the community is confused by this situation. This research is a qualitative research with a scientific approach. Data sources were obtained based on interviews, observation and documentation, with descriptive analysis. The results of this study indicate that; 1) The method of determining the beginning of the Kamariah Month of the Majelis Pengkajian Tauhid Tasawuf Indonesia (MPTT-I) uses conventional rukyatul hilal, with a limit of 32 minutes of sunrise-sunset distance, 2) The implementation of matlak in determining the beginning of the Kamariah Month of the Majelis Pengkajian Tauhid Tasawuf Indonesia (MPTT-I) on the Potential Differences in Fasting and Feast Days in Indonesia is very significant, the application of this matlak has an impact on the impossibility of unification. With the consequence that it will be absolutely different from some methods such as imkanurrukyat with existing criteria.